ACCOUNTING’S STUDENTS SOFT SKILLS DEVELOPMENT IN INDUSTRIAL REVOLUTION 4.0 (CASE STUDY AT UNIVERSITIES IN BENGKULU) - Fenny Marietza; Joshuwah Oswandi (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2023)
Job competition in the era of the industrial revolution 4.0 requires accountants to have more skills in addition to the knowledge gained in college; these skills are called soft skills. However, the reality is that many accountants still lack master soft skills. This problem cannot be separated from the role of universities as providers of accounting graduates. This study aims to describe the role of universities, especially accounting study programs, in developing the soft skills of accounting students in the era of the industrial revolution 4.0. This research is qualitative research with a case study approach. The informants in this study were four managers of accounting departments, four managers of accounting student organizations, and one manager of MBKM centers working in 4 universities in Bengkulu City. The data used in this study was obtained through direct interviews with data analysis techniques in data collection, data reduction, data presentation, and conclusions. The results of this study show that Bengkulu City College has developed the soft skills of accounting students through soft skills courses, integrating soft skills development into learning, encouraging accounting students to participate in MBKM programs, organizational activities, seminars, FMD, training, and soft skills competency tests. This research helps the manager of the Bengkulu City accounting study program understand and re-evaluate the current state of soft skills development of accounting students so that it can be better in the future.